2013
DOI: 10.1186/2043-9113-3-18
|View full text |Cite
|
Sign up to set email alerts
|

Using biomarkers to predict progression from clinically isolated syndrome to multiple sclerosis

Abstract: BackgroundDetection of brain lesions disseminated in space and time by magnetic resonance imaging remains a cornerstone for the diagnosis of clinically definite multiple sclerosis. We have sought to determine if gene expression biomarkers could contribute to the clinical diagnosis of multiple sclerosis.MethodsWe employed expression levels of 30 genes in blood from 199 subjects with multiple sclerosis, 203 subjects with other neurologic disorders, and 114 healthy control subjects to train ratioscore and support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…We annotated both mRNAs and lncRNAs using respective references from gencode.v17 40 , 41 . To assess quantitative accuracy of our RNA-seq analysis, we compared expression levels from one individual of 34 protein-coding genes determined by RNA-seq and by quantitative RT-PCR 42 . We found that quantitative transcript determinations were highly correlated across this gene set that exhibited a wide expression range (>10 4 ) ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We annotated both mRNAs and lncRNAs using respective references from gencode.v17 40 , 41 . To assess quantitative accuracy of our RNA-seq analysis, we compared expression levels from one individual of 34 protein-coding genes determined by RNA-seq and by quantitative RT-PCR 42 . We found that quantitative transcript determinations were highly correlated across this gene set that exhibited a wide expression range (>10 4 ) ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…mRNA studies on the expression of immune and cytokine genes were performed from stored blood obtained from the Accelerated Cure Project (http://www.acceleratedcure.org/about) or the MS center at Vanderbilt and stored in PAX gene tubes. The details of these samples have been reported previously 8, 9, 29 . Flow cytometric assays were performed on freshly isolated peripheral blood mononuclear and serological assays on CSF and serum samples were obtained from stored samples obtained from the MS clinic.…”
Section: Methodsmentioning
confidence: 99%
“…These studies were based on our early studies examining the gene expression profiles of MS patients which showed an increased expression of genes which participate in the innate immune response and the more recent studies showing the expression of IL-33 to be increased in MS 59 .…”
Section: Introductionmentioning
confidence: 99%
“…RA, inflammatory bowel diseases, multiple sclerosis, etc. (1215). To this end, we analyzed >1,500 CTRLs, subjects with different autoimmune diseases, and subjects with chronic non-inflammatory diseases (disease controls).…”
Section: Resultsmentioning
confidence: 99%